High‐Efficiency Sb2(S, Se)3 Solar Cells with New Hole Transport Layer‐Free Back Architecture via 2D Titanium‐Carbide Mxene. (27th November 2021) - Li, Hu; Lin, Limei; Yao, Liquan; Wu, Fengying; Wei, Dong; Liu, Guoliang; Huang, Zhigao; Chen, Shuiyuan; Li, Jianmin; Chen, Guilin
Abstract: MXene, a class of 2D materials of metal carbide or nitride, has attracted a lot of attention recently due to its excellent optical and electrical properties. In this work, titanium‐carbide MXene (Ti3 C2 T x ) is introduced as a back electrode in Sb2 (S, Se)3 thin‐film solar cells (FTO/CdS/Sb2 (S, Se)3 /MXene) for the first time, which displaces traditional carbon (C) and gold (Au) electrodes entirely. Impressively, thanks to its high conductivity, mild reflectivity, and flexible flake architecture, the MXene‐based device performance outperforms typical C and Au electrodes by 153% and 77%, respectively. Specifically, the tunable work function of MXene and a beneficial Sb–O bond formed between Sb2 (S, Se)3 and MXene efficiently suppress the recombination and enhance charge transport by enjoying the unique merit of the rich terminal groups of MXene. As a result, the best efficiency of 8.29% of MXene‐based Sb2 (S, Se)3 solar device is achieved, which represents the highest performance of noble metal and/or hole transport layer‐free derived Sb2 (S, Se)3 solar cells to date. This result has revealed that MXene is a feasible material to substitute the back electrode in Sb‐based solar cells to reach high efficiency, low cost, and high stability. Abstract : MXene (Ti3 C2 T x ), a 2D material with high conductivity, mild reflectivity, flexible flake design, and configurable work function, is used as a novel type of back contact material in Sb2 (S, Se)3 planar solar cells for the first time. Thus, a noble metal and/or hole transport layer‐free antimony‐based device with a high efficiency of 8.29% is presented.